Uptake of Cost-Free Hepatitis B Vaccination among Healthcare Workers in Northern Tanzania (Tanzania Medical Journal, 2021)
BackgroundThe World Health Organization and other global agencies recommend all healthcare workers (HCWs) to get vaccinated against hepatitis B virus before enrolment to clinical work. There are limited data in low-income countries on hepatitis B virus vaccination coverage among HCWs, which set back WHO Hepatitis B Elimination Strategy 2016-2021. The aim of this study was to determine the prevalence of hepatitis B virus vaccination uptake and associated factors among HCWs from a tertiary and teaching hospital in northern Tanzania.MethodsA cross-sectional study was conducted among HCWs at Kilimanjaro Christian Medical Centre a referral and teaching hospital from August 2016 to June 2017. Questionnaire based interviews were used to obtain information about HCWs’ demographic characteristics, occupation risks and other invasive procedures such as intravenous, and intramuscular injections and knowledge of Hepatitis B Virus (HBV) infection. Multivariable logistic regression was used to determine factors associated with Engerex DNA-recombinant hepatitis B vaccine uptake.ResultsAbout two third 295 (67.4%) of 438 participants had received HBV vaccination. Among those who ever received HBV vaccination (n=295), 205 (70.5%) received 3 shots, 57 (19.5%) received 2 shots and 33 (10%) received 1 shot. HCWs working in clinical areas had 79% higher odds of vaccine uptake compared to those who were not (OR=1.79, 95%CI 1.11, 2.89). Ever having intravenous and intramuscular injections significantly increased the odds of vaccination uptake compared to those who never had (OR=2.21, 95%CI 1.33, 3.66) and (OR=2.42, 95%CI 1.36, 4.28) respectively. Also, HCWs with a fair and good knowledge on HBV infection had over three times higher odds of vaccine uptake compared to those with poor knowledge (OR=3.08, 95%CI 1.90, 5.01) and (OR=3.07, 95%CI 1.75, 5.40), respectively. After adjusting for other factors, those that remained to be significantly associated with HBV vaccine uptake were area of specialty and knowledge on HBV infection.ConclusionThe current Engerex DNA-recombinant hepatitis B vaccine coverage among HCWs at KCMC, referral and teaching hospital in North-eastern Tanzania was only 67.4% despite of it been given free of charge. Factors that were associated with HBV vaccine uptake include area of specialty and knowledge of participants on HBV infection and vaccination. We encourage continuous medical education among HCWs about importance of hepatitis B vaccination. We also recommend hepatitis B vaccination as pre-employment requirement for HCWs as well as doing antibody titer determination post vaccination.Keywords: Cost-free hepatitis B vaccine, Prevention, Healthcare workers, vaccination coverage, Low income countries, Tanzania.